Systematic review with meta‐analysis: high prevalence and cost of continued aminosalicylate use in patients with ulcerative colitis escalated to immunosuppressive and biological therapies. Issue 4 (19th December 2018) - Ma, Christopher; Guizzetti, Leonardo; Cipriano, Lauren E.; Parker, Claire E.; Nguyen, Tran M.; Gregor, James C.; Chande, Nilesh; Feagan, Brian G.; Jairath, Vipul
Summary: Background: Aminosalicylates are the most frequently prescribed treatment for ulcerative colitis (UC). In the absence of empirical evidence, clinicians are uncertain whether to continue aminosalicylates in patients with UC after escalating therapy. Aims: To quantify concomitant aminosalicylate use in UC randomised clinical trials (RCTs), identify factors associated with their use, and estimate treatment costs of concomitant aminosalicylate therapy. Methods: MEDLINE, Embase, and CENTRAL were searched from inception to 1 March 2017 for placebo‐controlled RCTs of immunosuppressants, biologics, or oral small molecules in adults with UC. The proportion of patients prescribed concomitant aminosalicylates at trial entry was pooled using a random‐effects model. Meta‐regression was performed to assess trial‐level factors associated with aminosalicylate use. Treatment costs were estimated using 2018 formulary data from five Canadian provinces. Results: Thirty‐two trials were included (23 induction only, nine induction, and maintenance trials). The pooled proportion of patients co‐prescribed aminosalicylates was 80.7% (95% CI 75.5%‐85.1%), with considerable observed heterogeneity ( I 2 = 95%). In univariable meta‐regression, aminosalicylate use was not associated with trial design, setting, year of publication, disease severity, disease duration, or drug class. The estimated direct annual treatment cost of concomitant aminosalicylates is 20 million for the Canadian UC population, assuming conservative estimates of UC prevalence, aminosalicylate use and dose, and the lowest cost formulation. Conclusions: Approximately 80% of UC patients entering clinical trials of immunosuppressants, biologics, or oral small molecules continue to use aminosalicylates. An RCT is needed to inform the benefits and harms of continuing vs stopping aminosalicylates in patients escalating therapy.